Solar Energy and Heat Storage - Nordell, Bo; Söderlund, Monika (Luleå tekniska universitet, Arkitektur och vatten, 1991)
This book was originally published at Luleå University of Technology in 1987 fulfilling a need within Sweden to disseminate the techniques of alternative heating using solar energy in association with energy storage. In the year 2000 it was realised that the book required updating. This second edition contains a number of changes that bring it up to date, and at the same time, it was made accessible to a much wider audience by being translated into English. Text book for Civil Eng. Program. Division of Water Resources Engineering. Luleå University of Technology.